Alguns resultados acerca da termodinâmica de buracos negros no contexto da Rainbow Gravity - Silva, Gislaine Varão da (2022)
In this Master thesis we will discuss some questions related to the thermodynamics of black holes, in the context of a modified version of General Relativity which is termed Rainbow Gravity. Thus, we will analyse the thermodynamics of Kiselev black holes, taking into account different kind of fluids surrounding charged and uncharged black holes with cosmological constant. Particularly, we will study the existence remanescent black holes and the Joule-Thompson effect, along with an approach known nowdays as thermochemistry of black hole.